Severe Acute Kidney Injury and Mortality in Extremely Low Gestational Age Neonates. Issue 6 (June 2021) - Hingorani, Sangeeta; Schmicker, Robert H.; Brophy, Patrick D.; Heagerty, Patrick J.; Juul, Sandra E.; Goldstein, Stuart L.; Askenazi, David
Visual Abstract: Abstract : Background and objectives: AKI is associated with poor short- and long-term outcomes. Questions remain about the frequency and timing of AKI, and whether AKI is a cause of death in extremely low gestational age neonates. Design, setting, participants, & measurements: The Recombinant Erythropoietin for Protection of Infant Kidney Disease Study examines the kidney outcomes of extremely low gestational age neonates enrolled in the Preterm Epo Neuroprotection study, a randomized, placebo-controlled trial of recombinant human erythropoietin. We included 900 of 941 patients enrolled in Preterm Epo Neuroprotection. Baseline characteristics were compared by primary exposure (severe AKI versus none/stage 1 AKI) using unadjusted logistic regression models. Cox regression models estimated the relationship between severe AKI and death after adjustment for potential confounders. Time-dependent AKI was modeled as a binary outcome and a categorical variable by stage of AKI. We fit Cox models using time-dependent AKI status lagged by <7 days before death. Landmark analyses examined the relationship of death with development of severe AKI. Results: Severe AKI occurred in 168 of 900 (19%, 95% confidence interval, 17% to 20%) neonates, and stage 3 AKI occurred in 60 (7%, 95% confidence interval, 5% to 8%). Stage 3 AKI occurring 7 days before death (hazard ratio, 3.88; 95% confidence interval, 1.26 to 11.96), intraventricular hemorrhage (hazard ratio, 2.01; 95% confidence interval, 1.01 to 3.99) and sepsis (hazard ratio, 2.85; 95% confidence interval, 1.12 to 7.22) were all independently associated with death. Severe AKI occurring 7 days before death (hazard ratio, 2.21; 95% confidence interval, 0.92 to 5.26) was associated with death but not statistically significant. In a landmark analysis, after adjusting for potential confounders, late (after day 14 and before day 28) severe AKI was strongly associated with higher hazard of death (hazard ratio, 4.57; 95% confidence interval, 1.82 to 11.5). Conclusions: Severe AKI occurs frequently in extremely low gestational age neonates. Stage 3 AKI is associated with mortality, and this association is present 7 days before death.